Influences of age-related positivity effect on characteristics of odor-evoked autobiographical memories in older Japanese adults - Yamamoto, Kohsuke; Sugiyama, Haruko (Frontiers in Psychology, 2023)
Older adults tend to remember past life events more positively than younger adults. This tendency is the age-related positivity effect. The present study examined whether this effect occurred for odor-cued autobiographical memories. Three-hundred and seventeen young and 181 older Japanese participants were asked to remember autobiographical events cued by odors. Participants then completed the Odor-Evoked Autobiographical Memory Questionnaire (OEAMQ). In the results, older participants recalled more positive memories than younger participants. Older participants also rated the OEAMQ subscales higher than the younger participants. Furthermore, there were significant positive correlations between the ratings of odor emotional characteristics and OEAMQ subscales. The age-related positivity effect was observed for odor-evoked autobiographical memories. The emotion aroused by odor played a significant role in some attributes of odor-evoked autobiographical memory. The age-related positivity effect in odor-cued autobiographical memories has important implications for understanding the influence of aging on autobiographical memories.